Optimization of spray drying parameters for the preparation of Carrot milk powder - Kandula, Sravani; Narayanan, Rita (Indian Journal of Dairy Science, 2019)
In this study a novel carotene enriched milk powder was developed using skim milk and carrots. In recent years, contributions of spray drying in food manufacturing has gained considerable interest compared to other conventional drying methods mainly due to their cost efficiency and enhanced shelf life of the product. In the present study, inclusion of 40 per cent of carrot juice to skim milk (CS3) was adjudged as the optimum level based on sensory evaluation for the preparation of standardized mix. The mix was spray dried using laboratory model spray drier at different inlet temperatures viz., 165oC, 170oC and 175oC with feed flow rates of 0.2 kg/hr, 0.25 kg/hr and 0.3 kg/hr respectively, keeping a constant outlet temperature of 60oC and compressed air pressure of 2 kg/cm2. The inlet and outlet air temperatures of 170oC and 60oC with feed flow rate of 0.25 kg/hr and compressed air pressure of 2 kg/cm2 were found optimum after assessing the moisture content of the powder. The physical properties of the spray dried carrot milk powder were 0.535±0.008 g/cc for loose density, 0.606±0.003 g/cc for packed density, 0.000±0.000 ml for insoluble index and 0.378± 0.003 for water activity. The nutrient composition of carrot milk powder for protein, fat and fibre were 28.54, 3.90 and 1.73 g/100g respectively. Beta carotene content was 2038 mcg/100g which almost meets the recommended daily intake by ICMR suggested for 6- 12 months old. Vitamin A was 10 mcg/100g and Total Polyphenol Compounds (as Gallic acid) were 220 mg/100g. It can be concluded that this product serves as an instant carotene enriched powder that can be consumed by all age groups.